The impact of zakat contribution on the financial performance of Islamic banks in Malaysia - Rosman, Romzie; Haron, Razali; Mohamed Othman, Nurul Balqis (IIUM Press, International Islamic University Malaysia, 2019)
Islamic banks in Malaysia are beginning to response to calls for financial services that are responsible in providing social development impacts to the nation. Malaysia’s value-based intermediation strategy, initiated by the Bank Negara Malaysia is expected to move the Islamic finance industry to the next level of sustainable and long term economic development. Islamic banks are expected to not only focus on profit but also on contribution to societies through Islamic social finance. The traditional methods of Islamic social finance especially on the contribution of zakāt, waqf and ṣadaqah have been used to provide for the basic means of livelihood for the poor. Not only that, this shows that Islamic banks do not only concern on making profits but making contribution to the societies by involving in Islamic social finance through corporate social responsibility. Specifically, this study examines the impact of corporate social responsibilities particularly on the application of Islamic social finance which is zakāt contribution by Islamic banks on their financial performances namely return on assets, return on equity and operating profit. This study focuses on Islamic banks in Malaysia from 2011 to 2018. The financial information is extracted from Fitch Connect and annual reports of the respective Islamic banks which include 15 Islamic banks in Malaysia. The panel regression method was adopted to explain the three models and examine the impact of Islamic social finance on the financial performances of Islamic banks. The findings show that zakāt contribution has positive significant impact on Islamic banks’ financial performance namely operating profit. Hence, the findings of this study offer policy implications by providing empirical evidence on the importance of Islamic social finance on the financial performance of Islamic banks.